GAMBARAN LINGKUNGAN FISIK PADA SEKOLAH PENDIDIKAN ANAK USIA DINI (PAUD) DI KABUPATEN INDRAGIRI HILIR - Rajali, Rajali; Hasanah, Oswati; Woferst, Rismadefi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Introduction: The physical environment of the school is everything that is in it. The conditions of the components of the physical environment of the school can cause health and safety problems to children. This study aims to identify a picture of the physical environment of early childhood education (PAUD) schools in the kemuning sub-district, indragiri downstream district with a descriptive research design. Methods: The sample in this study were 27 respondents, namely all early childhood education in kemuning sub-districts which were taken based on inclusion criteria using total sampling technique. The measuring instrument used was a questionnaire with observations of the physical environment which consisted of 12 categories. The analysis used was univariate analysis. Results: The results of the observational study found that several schools paid less attention to school health and safety, such as a leaky roof, no ventilation, no ceiling, windows but never opened, dirty and dusty floors, uneven walls, sanitary conditions inadequate and the page has sharp objects. Class roof category that met the requirements (88.9%), class ventilation that met the requirements (77,8%), class floors that met the requirements (96,3%), lighting that met the requirements (85.2%), class walls that meet the requirements (77.8%), class windows that meet the requirements (44.4%), room temperature that meets the requirements (88.9%), class ceilings that meet the requirements (66,7%), physical conditions of water that meet the requirements (96.3%), toileting that meets the requirements (66,7%), washing places that meet the requirements (51,9%) and pages that meet the requirements (96,3%). Conclusion: Can investigate this lesson to schools, because the physical environment of PAUD is the responsibility of the supervisor, so that environmental prevention can be managed properly.Keywords: Overview, physical environment, (PAUD).